Leveraging nano silica and plant growth promoting rhizobacteria (PGPR) isolated from Gangetic riparian zone to Combat Pendimethalin Toxicity in Brassica juncea - Samarth Sharma; Sneha Tripathi; Kavita Tiwari; Shivani Mahra; Shivesh Sharma (Plant Nano Biology)
The aim of this study is to explore novel plant growth-promoting rhizobacteria (PGPR) isolated from Gangetic riparian zones and investigates their role in enhancing the resilience of Brassica juncea to pendimethalin toxicity using SiNPs (Silicon nanoparticles). The isolated PGPR was characterized by 16sRNA and its phylogenetic analysis revealed it as Bacillus pulumis. Isolate was examined for its plant growth promotion potential and stress alleviating capabilities. SiNP was utilized as a potential amendment to enhance these effects. Bacillus pulumis showed IAA production, ACC deaminase activity, phosphate solubilisation and siderophore production attributes. Fluorescence microscopy conducted in vivo confirmed the accumulation of reactive oxygen species (ROS), as supported by elevated MDA concentration and reduced membrane permeability. Exposure of Brassica juncea seedlings to 5 μM pendimethalin led to a marked increase in reactive oxygen species (ROS), with superoxide radicals (SOR) rising by 125.58 % and hydrogen peroxide (H₂O₂) by 159.32 % in roots, compared to the control. The combined application of PGPR and SiNP significantly mitigated this stress, reducing SOR and H₂O₂ levels to 27.91 % and 35.59 % respectively. This reduction is linked to enhanced antioxidant defence mechanisms, as the activities of superoxide dismutase (SOD) and catalase (CAT) increased by 22.76 % and 28.38 %, respectively, in root of seedlings co-treated with SiNP and PGPR. Pendimethalin alone reduced dehydroascorbate reductase (DHAR) and monodehydroascorbate reductase (MDAR) activity in roots by 28.95 % and 42.11 %, respectively. However, individual supplementation of SiNP and PGPR mitigated this suppression, with drop in DHAR activity reduced to only 12.63 % and 11.58 %, and MDAR by 17.54 % and 22.81 %, respectively. Co-application of SiNP and PGPR further alleviated this inhibition, limiting DHAR reduction to 9.47 % and MDAR to 3.51 %. This suggests that pendimethalin toxicity causes oxidative stress through disruption of redox balance and over production of ROS and the combined action of SiNP and PGPR enhances the antioxidant system, which likely explains the synergistic effect in alleviating pendimethalin-induced toxicity. The co-application of PGPR and SiNP significantly enhanced plant growth parameters, increased photosynthetic pigment content, improved membrane stability, and reduced lipid peroxidation in both leaves and roots. This research underscores the potential of PGPR and SiNP in sustainable agriculture, particularly in mitigating herbicide-induced stress in crop plants.